Fundoplication after lung transplantation in patients with systemic sclerosis–related end-stage lung disease. Issue 3 (October 2021) - Leiva-Juárez, Miguel M; Urso, Andreacarola; Costa, Joseph; Stanifer, Bryan P; Sonett, Joshua R; Benvenuto, Luke; Aversa, Megan; Robbins, Hilary; Shah, Lori; Arcasoy, Selim; D'Ovidio, Frank
Introduction: Gastroesophageal reflux and aspiration are risk factors for chronic lung allograft dysfunction in lung transplant recipients. Patients with systemic sclerosis are at an increased risk of aspiration due to esophageal dysmotility and an ineffective lower esophageal sphincter. The aim of this study is to understand the effect of fundoplication on outcomes in systemic sclerosis recipients. Methods: Between 2001 and 2019, 168 systemic sclerosis patients were referred for lung transplantation—51 (30.3%) were listed and 36 (21.4%) were transplanted. Recipients were stratified whether they underwent a fundoplication (n = 10, 27.8%) or not (n = 26, 72.2%). Freedom from chronic lung allograft dysfunction and survival were analyzed using log-rank test. Multivariable analysis for known risk factors was performed using a Cox-proportional hazards model. Results: Median time to fundoplication after transplantation was 16.4 months (interquartile range: 9.6–25.1) and all were laparoscopic (Dor 50%, Nissen 40%, Toupet 10%). There were no differences in acute rejection ⩾ A1 (26.9% vs 30%), or primary graft dysfunction grades 2–3 at 72 h (42.3% vs 40%) between groups. Recipients with fundoplication had an increased freedom from chronic lung allograft dysfunction (p = 0.035) and overall survival (p = 0.01). Fundoplication was associated with a reduced risk of mortality adjusting for other comorbidities (hazard ratio = 0.13; 95% confidence interval = 0.02–0.65; p = 0.014). Double and single lung transplant did not have different post-transplant survival. Conclusion: Fundoplication in systemic sclerosis lung transplant recipients is associated with greater freedom from chronic lung allograft dysfunction and overall survival. Screening for reflux and aspiration followed by early fundoplication may delay graft deterioration in this population.